Enhancement of the Biological and Mechanical Performances of Sintered Hydroxyapatite by Multiple Ions Doping - Sprio, Simone; Dapporto, Massimiliano; Preti, Lorenzo; Mazzoni, Elisa; Iaquinta, Maria Rosa; Martini, Fernanda; Tognon, Mauro; Pugno, Nicola M.; Restivo, Elisa; Visai, Livia; Tampieri, Anna (Frontiers in Materials, 2020)
In the present work, hydroxyapatite nanoparticles (HA) doped with Mg2+, Sr2+ and Zn2+ ions are developed by wet neutralization method and then sintered at 1250 °C to obtain bulk consolidated materials. Physicochemical and microstructural analyses show that the presence of ion doping in the HA structure induced the formation of betaTCP as secondary phase, during the sintering process, and we found that this effect is depending on the solubility and stability of the various doping ions in the hydroxyapatite lattice itself. We also found that the formation of betaTCP as secondary phase, in turn, confines the grain growth of HA induced by the high temperature sintering process, thus leading to a strong increase of the flexural strength of the bulk materials, according to Hall-Petch-like law. Furthermore, we found that the doping ions enter also in the structure of the betaTCP phase; besides the grain growth confinement, also the solubility and ion release ability of the final materials were enhanced. In addition to ameliorate the mechanical performance, the described phenomena also activate multiple bio-functionalities: i) ability to up-regulate various genes involved in the osteogenesis, as obtained by human adipose stem cells culture and evaluated by array technology; ii) enhanced resistance to the adhesion and proliferation of gram+ and gram- bacterial strains. Hence, our results open a perspective for the use of sintered multiple ion-doped HA to develop ceramic bio-devices such as plates, screws or other osteosynthesis media, with enhanced strength, osteointegrability and ability to prevent post-surgical infections.